A música como recurso pedagógico: uma experiência na educação infantil da escola EMEI Nossa Senhora de Nazaré - São Miguel do Guamá - Pará - RESENDE, Silvana do Socorro Tenório (2020)
This research project aims to investigate which educational practices through music that participate in the teaching process of pre-II children of the EMEI Nossa Senhora de Nazaré, in the municipality of São Miguel do Guamá-PA, and their contributions to the improvement of children's learning. The research is of qualitative nature adopting itself as method the Case Study. In order to collect data from the research, the open interview with 09 (nine) pre-II students, and / or a questionnaire with 03 (three) teachers, in May and June of 2018, were used as instruments. results. This work is based on the theoretical thoughts of Vigoski (2008), Moraes (2003), Pederiva (2009), Brazil (1998) and other scholars who discuss this theme. The study data reveal that music is an instrument that facilitates the teaching and learning process of students in the school under study, and is explored in association with diverse contents, through planning and socialization, as a tool to make the school a more joyful and receptive place . Since music is a tool that collaborates in the integral formation of the human being and through it the child comes into contact with the literate and playful world.